KFERQ-selective protein autophagy in Caenorhabditis elegans depends on LMP-1 - María Gallardo-Campos; Alicia N. Minniti; Juan Hormazabal; Gonzalo Núñez; Carlos F. Lagos; Tomás Perez-Acle; Rebeca Aldunate; Iván E. Alfaro (PLoS ONE, 2025)
Mammalian cells exhibit three autophagy mechanisms: macroautophagy, microautophagy (MIA), and chaperone-mediated autophagy (CMA), each employing unique mechanisms for transporting cellular material to the lysosome for degradation. MIA involves the engulfment of proteins via lysosomes/late endosomes through membrane invagination, while CMA directly imports cytosolic proteins into lysosomes, selectively targeting those harboring the KFERQ pentapeptide motif, helped by the chaperone HSC70. Despite the identification of several genetic markers of these pathways, our understanding of the underlying mechanisms, particularly in MIA and CMA, remains limited. To study CMA in vivo we designed a photoactivatable CMA reporter consisting of a plasmid encoding the KFERQ consensus signal for CMA targeting. We generated transgenic C. elegans strains with diverse genetic backgrounds to analyze the role of known molecular components of CMA in mammals. Additionally, we conducted an in-silico analysis of the structural interaction between C. elegans LMP-1 or LMP-2 proteins with the HSP-1 chaperone. Results: Our study shows a significant alteration in the distribution pattern of the KFERQ reporter in muscle cells upon induction of selective autophagy (CMA or MIA). We found that the reporter localized into lysosomes only during starvation, which abrogated in the absence of LMP-1. This study validates CMA in C. elegans and provides the development of a new tool for understanding selective autophagy mechanisms and their potential implications in various organisms.